CONTROVERSY ON RIBA PROHIBITION: MAQASHID SHARIAH PERSPECTIVE - Muhammad Iqbal Fasa; Itsla Yunisva Aviva; Yayan Firmansah; Suharto Suharto (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2019)
Riba is one of debated issues in modern times. Although the Qur'an forbids Riba, there are still Muslim scholars who are debated on the operational definition of Riba. Differences in opinion can be found in the repertoire of fiqh and tafsir al-Qur’an pre-modern and modern. Naturally, the debates are often influenced by the particular sociological context. There is existing view which distinguishes bank interest with usury, thus implies the permissibility interest rate in financial transactions. Prohibition of Riba, from the perspective of maqashid syariah, is based on moral considerations and humanity. It is because the essence of the prohibition is to eliminate of all forms of injustices and unfairness in economic practices. The method of this paper is based on literature review by reviewing in-depth the books, commentaries and writings on maqashid sharia, interest rate transaction, and usury.